Bacteriological, Biochemical, and Immunological Properties of Colostrum and Mature Milk From Mothers of Extremely Preterm Infants. Issue 1 (January 2015) - Moles, Laura; Manzano, Susana; Fernández, Leonides; Montilla, Antonia; Corzo, Nieves; Ares, Susana; Rodríguez, Juan M.; Espinosa-Martos, Irene
ABSTRACT Objectives: The objective of this work was to elucidate the influence of extremely premature birth (gestational age 24–27 weeks) on the microbiological, biochemical, and immunological composition of colostrum and mature milk. Methods: A total of 17 colostrum and 34 mature milk samples were provided by the 22 mothers of extremely preterms who participated in this study. Bacterial diversity was assessed by culture-based methods, whereas the concentration of lactose, glucose, and myo-inositol was determined by a gas chromatography procedure. Finally, the concentrations of a wide spectrum of cytokines, chemokines, growth factors, and immunoglobulins were measured using a multiplex system. Results: Bacteria were present in a small percentage of the colostrum and milk samples. Staphylococci, streptococci, and lactobacilli were the main bacterial groups isolated from colostrum, and they could be also isolated, together with enterococci and enterobacteria, from some mature milk samples. The colostrum concentrations of lactose and glucose were significantly lower than those found in mature milk, whereas the contrary was observed in relation to myo-inositol. The concentrations of most cytokines and immunoglobulins in colostrum were higher than in mature milk, and the differences were significant for immunoglobulin G3, immunoglobulin G4, interleukin (IL)-6, interferon-γ, interleukin-4 (IL-4), IL-13, IL-17, macrophage-monocyte chemoattractant protein-1 and macrophage inflammatory protein-1β. Conclusions: The bacteriological, biochemical, and immunological content of colostrum and mature milk from mothers of extremely preterm infants is particularly valuable for such infants. Efforts have to be made to try that preterm neonates receive milk from their own mothers or from donors matching, as much as possible, the gestational age of the preterm.